Mahāyāna Sūtras in Khotan - Chen, Ruixuan; Loukota Sanclemente, Diego (Indo-Iranian journal, 2018)
In this article we propose a series of twenty-three new identifications of sources for chapter 6 of the Book of Zambasta, whose tradent claims to have quoted a verse “from each sūtra.” In this installment we offer a detailed analysis of the first five newly identified quotations, highlighting their place within Mahāyāna and Khotanese literature.